STUDY OF DETERMINING PRAYER MAGHRIB TIME IN THE AL-FALAQIYYAH MANUSCRIPT - Zufialina, Era (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
The five daily prayer times in the al-Falaqiyah text are determined using rubū’ mujayyab, except for the Maghrib prayer time. It is stated in the text that the time for Maghrib is six o'clock without further information being given. This method contradicts the current method of determining the beginning of prayer times. By using qualitative research with literature study, this paper explores further the basis for calculations and implementation of the methods used in the al-Falaqiyyah text. By using descriptive analysis, it was found that the six o'clock provisions for Maghrib prayers in the text are approximate. After comparisons were made, there was also a difference of 3 to 7 minutes in the Maghrib time in the manuscript with the Maghrib time calculation using rubū’ mujayyab.